Discharge at Jarvis Creek, Interior Alaska, 2013-2016 - Liljedahl, Anna K. (Arctic Data Center, 2017)
The overall project assessed the linkages and controls of a subarctic glacier-permafrost hydrological system from a watershed-scale perspective using field measurements, remote sensing and numerical modeling. Jarvis Creek (634km2), which feeds the Delta and Tanana River in Interior Alaska, was studied as a proxy of the observed mountain glacier melting and permafrost degradation that has been documented across the Arctic region in recent decades. The specific objectives were to 1) assess the hydrologic fluxes (including streamflow source components), stores, pathways and the role of glacier wastage on watershed hydrology, through hydrologic and geochemical field measurements as well as numerical and statistical modeling; 2) quantify the effect of glaciers and permafrost on recent historical (1960-present) hydrologic fluxes and storage by combining remote sensing, field measurements of glacier mass balance, and hydrology with a heat- and mass transfer model, and 3) project the future hydrologic regime using custom-derived downscaled climate projections. The purpose of the dataset was to quantify the discharge from a glacierized headwater of the Yukon River basin and to assess any losses or gains in the lowland stream-reach. Discharge of the Jarvis Creek was measured sporadically and continuously at two locations starting in May 2011. The downstream site (364 km2 and 3% glacier cover) was located at near Jarvis Creek's confluence with the Delta River and the upstream site was located ~55km upstream where the stream exits the mountains (351 km2, 6% glacier cover). Measurements techniques included continuously measured stream water levels during the warm season in 2013 through 2016 and sporadic discharge measurements using three different sensors depending on flow conditions.